Transparent boundary conditions for the wave equation in one dimension and for a Dirac-like equation - M. Pilar Velasco; David Usero; Salvador Jimenez; Luis Vazquez (Electronic Journal of Differential Equations, 2015)
We present a method to achieve transparent boundary conditions for the one-dimensional wave equation, and show its numerical implementation using a finite-difference method. We also present an alternative method for building the same transparent boundary conditions using a Dirac-like equation and a Spinor-like formalism. Finally, we extend our method to the three-dimensional wave equation with radial symmetry.